2021
DOI: 10.1186/s13048-021-00808-x
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA AFAP1-AS1 facilitates ovarian cancer progression by regulating the miR-107/PDK4 axis

Abstract: Background Abnormally expressed in various tumors, long non-coding RNAs (lncRNAs) feature prominently in tumor development, yet little is still known regarding the functional roles of lncRNA AFAP1 antisense RNA 1 (AFAP1-AS1) in ovarian cancer (OC). Methods The relative expression levels of lncRNA AFAP1-AS1, microRNA (miR)-107 and pyruvate dehydrogenase kinase isozyme 4 (PDK4) mRNA were assessed by quantitative real-time PCR. PDK4, PCNA and cyclin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…For miR-107, only two recent studies provided data on biological functions in OvCa. The study by Tang et al [51] showed the ability of miR-107 to suppress proliferation and induce cell cycle arrest by targeting mRNA of CCNE1 (encodes cyclin E1), and the work by Liu et al [52] revealed that miR-107 inhibited cell proliferation, migration, and invasion in OvCa via targeting pyruvate dehydrogenase kinase isozyme 4 (PDK4). There were no data on the role of miR-107 in metastasis and on the clinical significance of this miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…For miR-107, only two recent studies provided data on biological functions in OvCa. The study by Tang et al [51] showed the ability of miR-107 to suppress proliferation and induce cell cycle arrest by targeting mRNA of CCNE1 (encodes cyclin E1), and the work by Liu et al [52] revealed that miR-107 inhibited cell proliferation, migration, and invasion in OvCa via targeting pyruvate dehydrogenase kinase isozyme 4 (PDK4). There were no data on the role of miR-107 in metastasis and on the clinical significance of this miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies have shown that aberrant expression of LncRNA is closely associated with OC occurrence and development, and LncRNAs are expected to be new markers for OC diagnosis and treatment [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of other miRNAs, namely miR-423-5p ( 33 ), miR-320a ( 34 ), miR-107 ( 35 ) and miR-384 ( 36 ) have been found to be sequestered by AFAP1-AS1 in different cancer tissues ( Figure 6 ).…”
Section: Cell Line Studiesmentioning
confidence: 99%